Students’ Cognitive Process In Problem Solving On Pattern Materials Reviewed From Math Anxiety - Muhammad Nanang Ferdiansyah; Rooselyna Ekawati (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
This study uses a qualitative descriptive approach that aims to describe the cognitive processes of students in solving problems in the number pattern material in terms of the level of students' mathematics anxiety. The instruments used in this study were the mathematics ability test (TKM) to control subject selection, the mathematics anxiety questionnaire (AKM), the problem-solving test (TPM), and the interview guidelines. From several 8th grade students, there are 21 male and 9 female students, one student was selected with a male student with high mathematical ability and high math anxiety and one male student with high mathematical ability and low math anxiety. The results showed that students with high and low math anxiety could solve problems, but there were differences in receiving, processing, storing, and recalling information. Students with low math anxiety check their answers again by processing the information in other ways, while students with high math anxiety do not. With the difference in the cognitive processes of students with math anxiety, teachers are advised to develop appropriate learning methods to reduce students' math anxiety, so that students can improve their thinking skills in mathematics at a higher level with low math anxiety. Keywords: Cognitive, Mathematical Ability, Math Anxiety, and Problem Solving